The Historical Thar Desert of India - Choudhary , Manisha (Mediterranean Journal of Social Sciences, 2021)
Desert was a ‘no-go area’ and the interactions with it were only to curb and contain the rebelling forces. This article is an attempt to understand the contours and history of Thar Desert of Rajasthan and to explore the features that have kept the various desert states (Jodhpur, Jaisalmer, Barmer, Bikaner etc.) and their populace sustaining in this region throughout the ages, even when this region had scarce water resources and intense desert with huge and extensive dunes. Through political control the dynasts kept the social organisation intact which ensured regular incomes for their respective dynasties. Through the participation of various social actors this dry and hot desert evolved as a massive trade emporium. The intense trade activities of Thar Desert kept the imperial centres intact in this agriculturally devoid zone. In the harsh environmental conditions, limited means, resources and the objects, the settlers of this desert were able to create a huge economy that sustained effectively. The economy build by them not only allowed the foundation and formation of the states, it also ensured their continuation and expansion over the centuries. The continuity of the Rajput states in the Thar Desert is sufficient indicators of the fact that this desert was nourishing all of them efficiently. Received: 14 May 2021 / Accepted: 28 June 2021 / Published: 8 July 2021